Sensitive, selective and rapid detection of 4,4′-methylenedianiline by surface-enhanced Raman spectroscopy using flower-like gold-silver nanoalloy embedded nickel-cobalt layered double hydroxide composites - Ge, Kun; Huang, Yihong; Zhang, Hanqiang; Gu, Ying (Sensors and actuators. B, Chemical, 2022)
In this paper, an ultra-sensitive and selective surface-enhanced Raman spectroscopy (SERS) substrate was designed and fabricated for rapid determination of 4,4′-methylenedianiline (4,4′-MDA) based on flower-like gold-silver nanoalloys embedded nickel-cobalt layered double hydroxide composites (NiCo/Au2Ag1). Flower-like NiCo-LDH with thin nanosheets were prepared via the hydrothermal method and the gold-silver nanoalloys were in-situ embedded on the surface of NiCo-LDH. The ultrahigh SERS activity of NiCo/Au2Ag1 was originated from the synergistic effect of electromagnetic and chemical mechanism induced by AuAg nanoalloys and NiCo-LDH, respectively. In addition, the flower-like of NiCo-LDH can provide more sites for AuAg and target molecules loading, further making highly sensitive SERS activity. The minimum detectable concentration for 4-mercaptobenzoic acid (4-MBA), crystal violet (CV) and Rhodamine 6 G (R6G) are 1.0 pg L−1 and 1.0 ng L−1 with enhancement factor (EF) of 1.2 × 1010, 1.7 × 108 and 1.1 × 108, respectively. The theoretical simulations and experiment results can further confirm the high SERS performance of NiCo/Au2Ag1 and superiority of NiCo-LDH compared to Ni(OH)2 and Co(OH)2. Good selectivity and anti-interference for 4,4′-MDA indicates great potentials in contaminants screening and detection. Subsequently, the NiCo/Au2Ag1 composites were used to determine group 2B carcinogen of 4,4′-MDA in water samples and indoor dust. The fabricated NiCo/Au2Ag1 substrate show good satisfied linearity (5.0–750.0 μg L−1) with low limits of detection (LOD) of 1.5 μg L−1, and the practical applications in environmental samples were obtained with good rapidity and accuracy. The developed NiCo/Au2Ag1 offers a novel strategy for fabricating SERS substrates with high sensitivity and selectivity in rapid monitoring of environmental pollutants. Herein, we introduced flower-like gold-silver nanoalloys embedded nickel-cobalt layered double hydroxide composites (NiCo/Au2Ag1) for determination of 4,4′-methylenedianiline (4,4′-MDA) in environmental water samples and indoor dust by surface-enhanced Raman spectroscopy (SERS) with high sensitivity and selectivity. [Display omitted] •The flower-like NiCo/Au2Ag1 composites were synthesized by in-situ reduction method.•The EF for 4-MBA, CV and R6G are 1.2 × 1010, 1.7 × 108 and 1.1 × 108.•The sensitivity and selectivity were investigated by DFT simulations.•The practical applications were achieved for 4,4′-MDA detection in environmental samples.